Kinerja Drainase terhadap Pembangunan Perumahan di Kelurahan Kasang Jaya Kecamatan Jambi Timur - Muhammad Guntur; M Farandika Akbar; Putri Mayasari (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2026)
This study aims to analyze the impact of residential development on the drainage system performance in Kasang Jaya Subdistrict, East Jambi District. The research employed a hydrological analysis using the Modified Rational Method to estimate design flood discharge and a hydraulic analysis using HEC-RAS software to evaluate the capacity of the existing drainage channels. The results show that residential development significantly increases the design flood discharge from 1.459–1.684 m³/s to 3.262–3.766 m³/s for 2–20-year return periods. Hydraulic simulations indicate that the existing drainage system is unable to accommodate the increased discharge, resulting in overflow and inundation at all observed points in the upstream, midstream, and downstream sections. This condition is further exacerbated by sedimentation and uncontrolled vegetation growth, which reduce the effective channel capacity. Consequently, the existing drainage system is no longer adequate to handle runoff generated by land-use changes. Therefore, integrated mitigation measures are required, including channel normalization, routine maintenance, and the construction of retention ponds as flood control infrastructure to reduce inundation risks in residential areas